1968
DOI: 10.1021/j100851a031
|View full text |Cite
|
Sign up to set email alerts
|

Composition of electrosorbed methanol

Abstract: The composition of the dehydrogenated species formed when methanol adsorbs from acid solution onto a smooth Pt electrode is examined by electrochemical techniques. Use is made of the fact that adsorption of methanol and oxidation of the adsorbed species can be studied separately. This allows determination of the charges involved in adsorbing (Qads) and stripping off (Qox) a given quantity of adsorbed intermediate. Qad. is measured by integration of current-time curves for methanol adsorption and Qox by linear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Kazarinov et al (19), $*e using a radiotracer technique, have shown that the oxidation of CH3OH, HCHO, and HCOOH, in both acid and alkaline electrolytes, results in the formation of C OH intermediates. This is in agreement with the results of Wieckowski (20), Breiter (21), Biegler (22), and Capon and Parsons (7). Vassilyev et al (23) showed how C OH could arise from a whole variety of organic molecule oxidations.…”
Section: Hcooh + Cooh-> C(oh)2 + Co= + H + E [7]supporting
confidence: 92%
“…Kazarinov et al (19), $*e using a radiotracer technique, have shown that the oxidation of CH3OH, HCHO, and HCOOH, in both acid and alkaline electrolytes, results in the formation of C OH intermediates. This is in agreement with the results of Wieckowski (20), Breiter (21), Biegler (22), and Capon and Parsons (7). Vassilyev et al (23) showed how C OH could arise from a whole variety of organic molecule oxidations.…”
Section: Hcooh + Cooh-> C(oh)2 + Co= + H + E [7]supporting
confidence: 92%
“…The effect of C 0 2 on the current-potential behaviour was studied by conducting the experiments described above under an atmosphere of COa, rather than argon. C 0 2 is electro inactive at the potentials of interest, but reacts with an intermediate of the H+ reduction, namely adsorbed H ', to give an adsorbed 'reduced' C 0 2 species (Giner 1963;Brummer 1966;Breiter 1967;Biegler 1968;Breiter 1968;Brummer & Cahill 1968;Kamath & Hira Lai 1968;Brummer & Cahill 1969;Stonehart 1973;Sobkowski & Czerwinski 1974Andreev et at. 1982;Beden et at.…”
Section: (Ii) Amperometric Measurements O F H+mentioning
confidence: 99%
“…In fact, the reverse is the case except in the approach to steady state (Figures 1-4 Composition of -Type. We have discussed the literature concerning the likely composition of "reduced C02"-similar to O-type11•30-in recent publications.31 •32 The basic controversy concerns whether that species is [33][34][35] or is not31•36 similar to adsorbed CO.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%